PENERAPAN MODEL PEMBELAJARAN INKUIRI TERBIMBING DENGAN VIDEO BERBASIS KONTEKSTUAL DALAM PEMBELAJARAN IPA PADA MATERI SUHU DAN PENGUKURANNYA DI SMP - Afrizal Fairuzabadi; Trapsilo Prihandono; Pramudya Dwi Aristya Putra (JURNAL PEMBELAJARAN FISIKA, 2017)
Guided inquiry is the application of constructivism learning theory which is based on scientific examination and investigation. The purposes of this research are too: (1) examine the differences in students science learning result using guided inquiry learning model with contextual-based video and learning model commonly used in SMP; (2) describe students activities; (3) describe students motivation. This research is a kind of experimental research which uses randomized post-test only control group design. The samples of this research are the students of class VII at SMPN 7 Jember, i.e. class VII B as a control class and class VII C as an experimental class. The data were analyzed using Independent Sample T-test in SPSS 16 to show differences between experimental class and control class. The results of this research are: (1) there are differences in students science learning result using guided inquiry learning model with contextual-based video and learning model commonly used in SMP; (2) the percentage of students activities is 87.81%; and (3) the percentage of students motivation is 85.77%.